Torque ripple minimization of rotating pole piece concentric magnetic gear using rotor skewing and pole piece modification - Mohd Ab Halim, Mohd Firdaus; Ab Rahman, Azhan; Mohd Anuar, Mohd Khairol Nizam; Mokhtar, Mohd Hisham (Taylor's University, 2025)
Rotating pole piece magnetic gear (RPMG) produces higher average torque than the conventional concentric magnetic gear (CMG). However, it also exhibits a higher torque ripple at the outer rotor as a result of switching of the rotating component from the outer pole pair (OPP) to the ferromagnetic pole piece (FMP). This paper explores a torque ripple suppression strategy through rotor skewing applied to the inner pole pair (IPP), outer pole pair (OPP), and ferromagnetic pole piece (FMP). Additionally, this study evaluates the impact of four distinct FMP shapes on the RPMG torque profile. Two gear ratio structures were tested at 4.33 and 5.66 ratio using 2D JMAG Designer finite element software. When skewing was performed on the IPP, it is observed that the inner torque ripple was reduced in both gear ratios when compared to the original structure with a slight drop in average torque for both rotors and gear ratios. Similarly, when smooth shape FMP was used in RPMG, it produced nearly the same average torque and slightly minimized the torque ripple in both gear ratios versus the original structure. The inner torque ripple was reduced to 2.9% at a 4.33 gear ratio and 4.1% at a 5.66 gear ratio, compared to the original structure. This improvement resulted in a slight average torque decrease of 1-2.5% across both rotors and gear ratios. Theoretically, simulation results have shown that rotor skewing, and FMP shape modification could minimize the torque ripple in RPMG especially at the inner rotor with moderately declined average torque for EV application where minimizing torque ripple is essential for smoother driving experience and reducing mechanical stress on components.